2004
DOI: 10.1002/pat.530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grass fiber filler on curing characteristics and mechanical properties of natural rubber

Abstract: Natural rubber is reinforced with a novel type of grass fiber (Cyperus Tegetum Rox b). The effects of fiber loading of different mesh sizes on curing characteristics and mechanical properties of grass fiber filled natural rubber composite are studied. Since 400 mesh grass fiber loaded natural rubber composite shows superior mechanical properties, therefore the effect of silane coupling agent was studied for this particular composite. Here composites were prepared by using water leached grass fiber. Optimum cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 20 publications
5
30
0
3
Order By: Relevance
“…These results corroborate those reported in the literature 32,34 , which indicate that the use of natural fibers as a reinforcement in natural rubber matrices increases the tensile modulus; this may be indicative of the excellent interactions between the fiber surface and the natural rubber matrix. 32,33 …”
Section: Mechanical Propertiessupporting
confidence: 92%
“…These results corroborate those reported in the literature 32,34 , which indicate that the use of natural fibers as a reinforcement in natural rubber matrices increases the tensile modulus; this may be indicative of the excellent interactions between the fiber surface and the natural rubber matrix. 32,33 …”
Section: Mechanical Propertiessupporting
confidence: 92%
“…In the past, a variety of short natural fibers were incorporated into natural rubber, and their reinforcement was discussed. [4][5][6][7][8][9][10] It was reported that they did not provide the same level of reinforcement compared to carbon black and silica; that is, the tensile strength and elongation at break of natural-rubber-based composites substantially decreased with the addition of natural fibers. In many cases, the loading of fibers that gave optimal fiber orientation and acceptable mechanical properties was found to be 20-30 phr.…”
Section: Introductionmentioning
confidence: 99%
“…7 Cellulose fibers like grass fiber and cotton fiber have also been used as the filler for fabrication of NR-based composites. 8,9 The recent approach has been to use nanosize fillers for the enhancement of properties. [10][11][12][13] Synthetic degradable fibers attracted scientist's attention because of their potential application in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%